Influence of breeding and length of feeding period on carcass characteristics and palatability of beef - Mackintosh, D.L.; Kropf, Donald H.; Flectcher, R.C.; Ahlschwede, G.A. (Kansas Agricultural Experiment Station, 2011)
During 1962-63, in cooperation with the American Hereford Association, 76 head of Hereford steers, sired by four different bulls, were slaughtered in Kansas City and the rib cut from 40 (10 from each sire group) was purchased for detailed analyses and palatability tests, a procedure following with all cattle on this phase of the project.
Keywords: Beef; Breeding; Carcass characteristics; Palatability; Marbling scores